Utility of the Hemangioma Severity Scale as a Triage Tool and Predictor of Need for Treatment. Issue 1 (16th December 2016) - Mull, Jamie L.; Chamlin, Sarah L.; Lai, Jin‐Shei; Beaumont, Jennifer L.; Cella, David; Rancour, Elizabeth A.; Baselga, Eulalia; Haggstrom, Anita N.
Abstract: Background/Objectives: Infantile hemangiomas (IHs) are commonly encountered in primary care and most often remain asymptomatic, resolving without sequelae. Certain characteristics are associated with a greater risk of complications, associated anomalies, and disfigurement. The heterogeneous presentation poses a clinical challenge for physicians in determining the need for treatment and subspecialty referral. This study aims to evaluate the utility of the previously published Hemangioma Severity Scale (HSS) to predict the need for treatment. Methods: This retrospective study included 106 patients with IHs seen in the Indiana University Dermatology Clinic in 2011. Data from electronic medical records and clinical photographs taken at patients' initial visits were used to score the hemangiomas using the HSS. Treatments used over 9 to 14 months of follow‐up were recorded. Results: Four HSS score subgroups were identified. Higher HSS scores correlated with the need for treatment; 98% of patients with HSS scores of 10 or greater received local or systemic therapy. Higher HSS scores also correlated with greater frequency of complications and risks of associated structural anomalies and permanent disfigurement. Scores did not correlate with sex, age at initial presentation, history of bleeding or pain, or IH size. Conclusions: The HSS may be a useful tool for primary care physicians in identifying high‐risk IHs that may benefit from therapy. This easy‐to‐use scale can improve clinical outcomes by identifying which patients need intervention to minimize complications. IHs with total HSS scores of 6 or greater should be referred for subspecialty evaluation.